An ultra-high-strength steel for an aircraft landing gear and a method for manufacturing the same

CN122382460BActive Publication Date: 2026-10-16BENGANG STEEL PLATES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610806250.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-10-16
Estimated Expiration
2046-06-05

AI Technical Summary

Technical Problem

[0003]目前公知的生产方式均是采用电弧炉冶炼+真空精炼+电渣重熔或更高成本的双真空冶炼,冶炼周期较长,成本高,很难满足连续性批量化生产的需求

Benefits of technology

1)通过添加微量微合金元素,利用固溶强化提高钢材的强度;在凝固过程中与钢中的N、C原子结合形成细小弥散强化相AlN、TiC、V4C3,在基体中阻碍晶粒的长大和晶界的迁移,细化晶粒,提高了强度和韧性;使强度显著提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122382460B_ABST
    Figure CN122382460B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of metal material and heat treatment technology, and particularly relates to a kind of super high strength steel for aircraft landing gear and a preparation method thereof. The present application is suitable for aircraft manufacturing. The chemical composition of the steel contains: C, Si, Mn, P≤0.012%, S≤0.004%, Cr, Mo, V, Ti, B, Alt, N, O≤0.0010%, and B / N=1.27-2.95, (Ce+Mg) / S=1.5-3.0, the balance being Fe and unavoidable impurities. The strength of the present application is not less than 1800MPa, the hardenability is J51-55, the impact toughness KV2≥160J. The steel has the characteristics of high strength, good wear resistance, high fatigue life, excellent welding performance, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the fields of metallic materials and heat treatment technology, and specifically relates to an ultra-high strength steel for aircraft landing gear and its preparation method. This invention is applicable to aircraft manufacturing. Background Technology

[0002] With the rapid development of the aerospace manufacturing industry, the demand for ultra-high strength steel is increasing. The original materials have defects such as low strength, poor toughness, and poor weldability, resulting in low fatigue performance and failing to meet the requirements. With the advancement and development of aircraft manufacturing technology, while reducing manufacturing costs, the requirements for material performance are also becoming increasingly stringent, requiring good hardenability, high strength and sufficient toughness after tempering, good machinability, and fatigue resistance.

[0003] Currently known production methods all employ electric arc furnace smelting + vacuum refining + electroslag remelting, or even more expensive double vacuum smelting. These methods have long smelting cycles and high costs, making it difficult to meet the demands of continuous mass production. Therefore, obtaining a high-efficiency, high-quality, and low-cost aerospace steel has become a focus for relevant enterprises. Both domestic and international efforts are exploring and expanding manufacturing methods to obtain aerospace steel plates with lower smelting costs, optimal alloying, best microstructure, and excellent comprehensive performance. This invention is developed against this backdrop. Summary of the Invention

[0004] This invention provides an ultra-high strength steel for aircraft landing gear and its preparation method. The steel has a strength of not less than 1800MPa, hardenability J51~55, and impact toughness KV2≥160J. The steel has the characteristics of high strength, good wear resistance, high fatigue life and excellent weldability.

[0005] To achieve the above objectives, the present invention employs the following technical solution: An ultra-high strength steel for aircraft landing gear has the following chemical composition by weight percentage: C: 0.35%–0.38%, Si: 1.22%–1.28%, Mn: 1.14%–1.29%, P≤0.012%, S≤0.004%, Cr: 1.44%–1.58%, Mo: 0.22%–0.28%, V: 0.05%–0.07%, Ti: 0.062%–0.074%, B: 0.0051%–0.0059%, Alt: 0.022%–0.054%, N: 0.0020%–0.0040%, O≤0.0010%, with B / N = 1.27–2.95, (Ce+Mg) / S = 1.5–3.0, and the balance being Fe and unavoidable impurities.

[0006] The residual elements in the steel are Pb+Sn+As+Sb+Bi≤0.02%.

[0007] The steel plate specifications are 3.0~16.0mm×1850~2150mm.

[0008] The tensile strength R of steel m ≥1800MPa, yield strength R p0.2 ≥1600MPa, elongation after fracture A 50 ≥12%, impact energy Kv2≥160J at -60℃, fracture toughness K1c≥150MPa.m 1 / 2 With a hardenability of J51-55, the corrosion rate of Q355B, a relatively low-alloy steel, is ≤35% in atmospheric conditions. It is a low-cost, high-hardenability, ultra-high-strength steel.

[0009] The reason for selecting the above alloying elements and their contents in this invention is as follows: Carbon (C) is one of the most effective elements for improving the hardness and strength of materials. Increasing the carbon content in steel will enhance its martensitic transformation ability, thereby improving its strength. However, excessively high C content can lead to severe central segregation, thus affecting the core properties of the steel plate. Furthermore, excessively high C content is detrimental to the toughness, ductility, and weldability of the material. This invention controls the C content to be between 0.35% and 0.38%.

[0010] Si (Si): Strengthens steel through solid solution treatment, enhancing its strength, hardness, and corrosion resistance. It is also a readily deoxidizing element in steel. Si accumulates on the steel plate surface, forming a dense oxide protective film that is tightly bonded to the matrix, effectively inhibiting the penetration of corrosive media; reducing the anisotropy of crystals; and forming Cr₂Si₃ hard phase particles with free Cr in the steel. Through control of the rolling process, micron-sized (15–40 μm) hard Cr₂Si₃ particles are dispersed and precipitated near grain boundaries or within grains, effectively improving the hardness and wear resistance of the steel. However, excessive Si can cause iron oxide red defects on the steel plate surface and also deteriorate the steel's plasticity and toughness. This invention specifies a Si content of 1.22%–1.28%.

[0011] Mn: Mn strengthens steel through solid solution to compensate for the strength loss caused by a decrease in carbon content, and is one of the most effective elements for improving hardenability and strength. However, excessive Mn content can easily lead to segregation in the center of the steel plate, reducing the impact toughness of the central region. It also increases the carbon equivalent, thus deteriorating weldability. In this invention, the Mn content is controlled at 1.14%–1.29%.

[0012] P and S: Harmful impurity elements in steel, which easily form defects such as inclusions and segregation. As impurity elements, they will adversely affect the plasticity, toughness, and weldability of the material, and their content should be minimized. This invention controls P ≤ 0.012% and S ≤ 0.004%.

[0013] Cr: Primarily enhances the strength and hardenability of materials through solid solution strengthening. Cr contributes more to increasing tensile strength than yield strength, effectively reducing the yield-to-tensile ratio. Simultaneously, Cr forms a continuous solid solution with Fe, providing solid solution strengthening, and forms various types of carbides with C, resulting in secondary strengthening effects. Therefore, this invention controls the Cr content to 1.44%–1.58%.

[0014] Mo: Improves the strength and hardenability of steel, overcomes temper brittleness during heat treatment to improve material properties, and forms fine and stable carbides (Mo2C). These carbides are more stable than Fe3C and are difficult to decompose and grow at high temperatures, hindering crystal migration and achieving a fine-grained effect. The refined grains can improve the low-temperature toughness of steel. This invention controls Mo content to be 0.22-0.28%.

[0015] V: plays a role in precipitation strengthening and precipitation strengthening in steel. VN, V(C,N) and V4C3 are mainly used as precipitation strengthening phases precipitated at low temperature to improve the strength of the material. In this invention, V is controlled at 0.05% to 0.07%.

[0016] Alt (Al): A strong deoxidizer in steelmaking, it helps refine grains and improve the strength and toughness of steel. However, Al reduces austenite stability and austenite undercooling, causing rapid growth of new phase nuclei, thereby reducing hardenability and increasing the critical quenching rate. Simultaneously, as a ferrite-forming element, excessive Al reduces steel plate strength and increases the brittleness of ferrite, leading to decreased toughness. This invention limits the Alt range to 0.022%–0.054%.

[0017] Ce and Mg: The purpose of adding them is to: (1) control the morphology, size and distribution of sulfide and oxide inclusions through Ce and Mg composite treatment, improve low-temperature toughness, and effectively improve the anisotropy of steel; (2) purify molten steel, improve the mechanical properties of the material, reduce the potential difference between inclusions and matrix, reduce the tendency of electrochemical corrosion caused by inclusions, and effectively improve the corrosion resistance of steel plates; (3) improve Cr segregation, promote the uniform precipitation of hard phases Cr7C3, Cr2C3 and Cr2Si3 and inhibit the aggregation and growth of this phase, thereby improving the wear resistance of steel plates; (4) the addition of Ce and Mg elements helps to inhibit the decomposition of residual austenite and the precipitation of carbides, which can significantly improve the plasticity and forming performance of steel plates, and facilitate the later processing and forming of materials. In this invention, (Ce+Mg) / S=1.5~3.0 is specified.

[0018] Ti: In steel, it is a strong C and N compound forming element, increasing the strength of the steel. During heating, Ti first forms TiN with N, inhibiting austenite grain growth and refining the grain size; it also forms fine carbides and carbonitrides with C and N, playing a precipitation strengthening role and increasing the strength of the material. This invention limits the Ti content to 0.062%–0.074%.

[0019] B combines with N to form BN particles. BN exhibits good stability and is not easily dissolved at high temperatures, thus reducing grain boundary brittleness. The B / N ratio is controlled to be 1.27–2.95. Furthermore, B segregates at austenite grain boundaries to suppress proeutectoid ferrite precipitation, allowing carbides to disperse and precipitate in the low-temperature region. In this invention, the B content is controlled at 0.0051%–0.0059%.

[0020] O and N: O forms oxide inclusions in steel, reducing the material's toughness and wear resistance. Generally, deoxidation treatment is required at the end of smelting to reduce oxide inclusions and bubbles, improving the internal quality of the steel and simultaneously enhancing material properties and low-temperature impact toughness. N, on the one hand, combines with Ti to form high-melting-point TiN particles, inhibiting excessive grain growth during heating. The fine precipitates have pinned grain boundaries, thus refining austenite grains. However, when the N content is too high, the high concentration of free N atoms causes failure, pinning dislocations and reducing toughness. On the other hand, N combines with Al to form AlN, disrupting the continuity of the steel matrix. This is especially true when AlN is abundant and aggregated, exacerbating the problem. Higher N content tends to accumulate at defects, worsening low-temperature impact toughness. Therefore, this invention controls the N content to 0.0020–0.0040% and O to ≤0.0010%.

[0021] Pb, Sn, As, Sb, and Bi are all residual elements in steel and have a significant impact on the embrittlement of steel plates. Within a controllable range, the lower the content, the better. This invention controls the content of Pb+Sn+As+Sb+Bi in steel to be ≤0.02%.

[0022] A method for preparing ultra-high strength steel for aircraft landing gear includes pre-desulfurization of molten hot metal, top-and-bottom blowing converter smelting, LF ladle furnace refining, slab continuous casting, continuous casting billet heating, hot continuous rolling, laminar flow cooling, and coiling, without using RH refining; the specific method includes: S1. Smelting: Top-and-bottom blown converter is used for smelting, with a scrap steel ratio of 41wt% to 48wt%, which is the green steel smelting process, resulting in pure steel. By limiting the scrap steel ratio, the carbon dioxide emissions during the preparation of ultra-high strength steel for aircraft landing gear are effectively reduced.

[0023] LF ladle furnace refining: When the molten steel reaches the LF refining treatment position, it is stirred by bottom blowing argon gas, and submerged arc slag, refining slag and lime are added. After the three-phase electrodes are energized and heated for 16 minutes, alloying elements are added for adjustment. According to the slag condition, aluminum granules and calcium carbide are added to make white slag. The energizing time is greater than 20 minutes, and the alloy composition is adjusted. Temperature is measured and samples are taken. After the composition and temperature meet the target requirements, soft blowing argon treatment is carried out to ensure that the soft blowing + calming time reaches 21 to 26 minutes, so that the inclusions can be fully floated and removed.

[0024] Slab continuous casting: A straight-arc continuous casting machine is used, and protective slag is used throughout the casting process to prevent the molten steel from contacting air. The thickness of the continuously cast slab is 230mm. Because Ce and Mg have strong affinity and easily form large amounts of complex compounds with O and S in the steel, affecting the fluidity of the molten steel, the feeding speed of Ce-Fe cored wire and Mg cored wire is specified as 16-18 m / min, and the feeding amount is 2.52-2.58 kg / t steel. The casting speed is controlled at 1.22-1.32 m / min. To reduce center segregation of the continuously cast slab, the superheat is controlled at 22-26℃. Electromagnetic stirring and dynamic light reduction technologies are also employed. The fixed length of the continuously cast slab is 11m.

[0025] S2. Heating of Continuously Cast Billets: This invention employs a composite strengthening method combining fine-grain strengthening, solid solution strengthening, and precipitation strengthening to improve material strength. Due to the addition of microalloying elements Cr, Ti, V, and B, a heating temperature of 1254–1274℃ is selected to ensure complete solid solution of BN, Ti(C, N), V(C, N), Cr2C3, and Cr7C3, aiming to achieve complete austenitization of the steel. The heating furnace is set to a weakly oxidizing atmosphere, with an air-fuel ratio between 1.1 and 1.2, and the heating time controlled between 126 and 146 minutes, including a soaking time of 32–42 minutes. Furthermore, the continuously cast billets are hot-charged after casting, and defect-free billets are directly transported to the heating furnace via roller conveyors for heating, effectively saving energy.

[0026] S3. Hot Continuous Rolling: Steel rolling employs a two-stage controlled rolling process. Roughing uses a high-temperature, high-reduction method, with an initial rolling temperature of 1122–1139℃ and a cumulative reduction rate of 72.4%–74.6%. This high reduction rate helps to compress defects in the cast billet and, through large deformation, forms more dislocations, thereby increasing the material's strength through dislocation strengthening. Finishing rolling has an initial rolling temperature of 1010℃–1120℃, which eliminates the adverse effects of dislocation strengthening on plasticity during roughing and ensures the sufficient precipitation of hard phases such as Cr7C3, Cr2C3, and Cr2Si3. During finishing rolling, all descaling water between stands, roll gap cooling water, inter-stand cooling water, and cross-spray water must be shut off. The final finishing rolling temperature is 904–924℃. To ensure the flatness and precision of the finished steel plate, the reduction rate of the final finishing pass is controlled at 10.2%–12.4%, and the plate crown is controlled at 45±5μm.

[0027] S4. Laminar flow cooling: Since the steel plate needs to be heat treated, water is not sprayed during the laminar flow cooling stage of this steel grade in actual production to ensure that the required F+P structure is obtained.

[0028] S5. Slow Cooling: After rolling, the steel coil is placed in a slow cooling pit for slow cooling for no less than 48 hours. The purpose is to eliminate internal stress and improve the uniformity of microstructure and properties by controlling the cooling rate.

[0029] S6. Heat Treatment: The process of normalizing + quenching + low-temperature tempering is adopted, and the process is as follows: normalizing temperature 874~889℃, holding temperature 25min~35min, air cooling; quenching temperature 912~928℃, holding temperature 30min~40min, oil cooling; strictly avoid the generation of microcracks during quenching; after quenching, perform low-temperature tempering in time, tempering temperature 280~300℃, holding temperature 20min~30min, air cooling, to ensure that the material has high strength while also having good toughness.

[0030] To achieve high strength and high toughness, this invention employs a Cr-Mo-B composition system. This system not only provides excellent corrosion resistance but also reduces the austenite phase region. Cr and Mo significantly decrease the diffusion rate of carbon in austenite, lowering the critical cooling rate and improving the hardenability of the steel plate. This allows the CCT phase transformation curve to shift significantly to the right, while also refining the microstructure, reducing weld crack sensitivity and the ductile-brittle transition temperature, thus significantly increasing strength. The addition of trace elements B and Mo hinders the formation of pearlite and the diffusion of carbon atoms during quenching, effectively improving hardenability and creating favorable conditions for martensite formation.

[0031] To meet the requirements of aircraft landing gear operating in complex environments, the steel plates must possess excellent corrosion resistance. This places higher demands on the uniformity of the steel's microstructure, its purity, and its gas content. The smelting process improves the surface and internal quality of the continuously cast billet and reduces steel defects by employing LF ladle furnace treatment, increasing soft blowing and calming times, inclusion modification treatment, and rational composition design. To ensure the cleanliness of raw materials, the sulfur content of the molten iron entering the furnace must be ≤0.003%. Sufficient LF treatment time is required to ensure adequate removal of nitrogen and oxygen gases from the steel. However, if the feeding methods for Ce-Fe alloy cored wire and Mg alloy cored wire are inappropriate, the spheroidization effect of inclusions will be insufficient. Therefore, this invention intentionally specifies (Ce+Mg) / S = 1.5~3.0.

[0032] The steel of this invention contains 1.22% to 1.28% Si. Si is a reactive element that readily reacts with oxygen in the air, exhibiting a passivating effect in natural environments. It can form a thin SiO2 film on the surface of the steel plate, thereby slowing down corrosion. Normally, Si is added to steel as a deoxidizing element. However, this invention has found that Si and Cr form intermetallic compounds in the steel. Under atmospheric corrosion conditions, these intermetallic compounds accumulate on the surface of the steel plate, effectively preventing corrosion.

[0033] The microstructure of the hot-rolled ultra-high strength steel for aircraft landing gear described in this invention, by area percentage, is 53%–58% ferrite and 42%–47% pearlite. The ferrite matrix contains a large number of spherical Mn-O-Cr-Mo-BN composite inclusions, as well as composite inclusions of Ce, Mg, S, and O. It also contains a large number of TiC, Ti(C, N), and BN precipitates with a size smaller than 9.0 nm. These composite inclusions and precipitates precipitate in the inner and outer rust layers of the steel plate, improving its corrosion resistance.

[0034] Compared with the prior art, the beneficial effects of the present invention are: 1) By adding trace amounts of microalloying elements, the strength of steel is improved by solid solution strengthening. During solidification, they combine with N and C atoms in the steel to form fine and dispersed strengthening phases AlN, TiC, and V4C3, which hinder grain growth and grain boundary migration in the matrix, refine the grains, and improve strength and toughness, thus significantly increasing the strength.

[0035] 2) The present invention also improves hardenability by adding trace elements B and Mo to hinder the formation of pearlite and the diffusion of C atoms during quenching, thereby creating favorable conditions for the formation of martensite.

[0036] 3) Under the premise of ensuring quality, the converter + ladle refining + continuous casting process is adopted, and the refining adopts LF furnace ladle refining to reduce the RH process; compared with the electric arc furnace + refining furnace + electroslag remelting process, the production cost is significantly reduced.

[0037] 4) This invention produces aircraft landing gear steel with lower smelting costs, the most reasonable alloying, the best microstructure, and excellent comprehensive performance. Attached Figure Description

[0038] Figure 1 This is a microstructure diagram (F+P) of the hot-rolled state in Example 1 of the present invention.

[0039] Figure 2 This is a microstructure diagram of the inclusions in Embodiment 1 of the present invention (BT0.5DT0.5).

[0040] Figure 3 This is a microstructure diagram (structure M) after heat treatment in Example 1 of the present invention.

[0041] Figure 4 The hardenability test curves of ultra-high strength steel in Examples 1 to 4 of this invention are shown. Detailed Implementation

[0042] The present invention will be further described in detail below with reference to the embodiments, but the scope of protection of the present invention is not limited thereto. Experimental methods for which specific conditions are not specified in the embodiments are generally determined according to national / industry standards; if there is no corresponding national / industry standard, then they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.

[0043] The high hardenability ultra-high strength steel for aircraft landing gear provided by this invention enhances strength by adding trace amounts of Si, Mn, Cr, and Mo elements and utilizing the principle of substitution solid solution strengthening. By adding trace amounts of Ti and V elements, they preferentially combine with N and C atoms during solidification to form fine and dispersed strengthening phases such as AlN, TiN, V4C3, and BN. These phases inhibit grain boundary movement and grain growth in the matrix, thus refining the grain size.

[0044] The present invention will be further described in detail below with reference to the embodiments, wherein the microstructure (F+P) of the hot-rolled steel plate in Embodiment 1 is shown below. Figure 1 The microstructure of inclusions in the steel in Example 1 is shown below. Figure 2 The microstructure of the heat-treated steel plate in Example 1 is shown below. Figure 3 (Organization M); The hardenability test curves of ultra-high strength steels in Examples 1 to 4 are shown in the figure. Figure 4 .

[0045] Example 1:

[0046] A high-hardenability ultra-high-strength steel for aircraft landing gear has the following chemical composition by mass percentage: C: 0.36%, Si: 1.26%, Mn: 1.20%, P: 0.007%, S: 0.004%, Cr: 1.45%, Mo: 0.24%, V: 0.05%, Ti: 0.072%, B: 0.0058%, Alt: 0.032%, N: 0.0026%, O: 0.0006%. Further, B / N = 2.0, (Ce+Mg) / S = 2.8, with the balance being Fe and unavoidable impurities. Additionally, the residual elements Pb+Sn+As+Sb+Bi in the steel ≤ 0.02%.

[0047] The method for preparing the high-hardenability ultra-high-strength steel for aircraft landing gear includes the following steps: The refining process uses an LF ladle furnace, which reduces the RH process and lowers costs. S1. Smelting: Top-and-bottom blown converter is used for smelting. The scrap steel ratio is 46%, and the steel is pure. By limiting the scrap steel ratio, the carbon dioxide emissions in the preparation process of ultra-high strength steel for aircraft landing gear are effectively reduced.

[0048] Ladle furnace refining: Molten steel undergoes LF refining treatment, bottom blowing argon agitation, and the addition of submerged arc slag, refining slag, and lime. After heating for 16 minutes by energizing the three-phase electrodes, alloying elements are added for adjustment. Depending on the slag condition, aluminum granules and calcium carbide are added to create white slag. The energizing time is 22 minutes to adjust the alloy composition. Temperature is measured and samples are taken. If the composition and temperature meet the target requirements, soft blowing argon treatment is performed to ensure that the soft blowing + calming time reaches 25 minutes, so that inclusions can be fully floated and removed.

[0049] Continuous casting: A straight-arc continuous casting machine is used, with protective slag used throughout the process to prevent contact between the molten steel and air. The thickness of the continuously cast billet is 230mm. The feed rate of Ce-Fe cored wire is 16m / min, and the feed rate of Mg cored wire is 17m / min. The feed rate of Ce-Fe is 2.54kg / t steel, and the feed rate of Mg is 2.52kg / t steel. The casting speed is controlled at 1.24m / min. To reduce center segregation of the continuously cast billet, the superheat is controlled at 25℃, and electromagnetic stirring and dynamic light reduction technologies are used. The fixed length of the continuously cast billet is 11m.

[0050] S2. Heating: To ensure sufficient solid solution of BN, Ti(C,N), V(C,N), Cr2C3, Cr7C3, etc., the heating temperature is selected as 1255℃, the heating furnace is set to a weak oxidizing atmosphere, the air-fuel ratio is set at 1.1, and the heating time is controlled at 130min, of which the soaking time is 32min. The continuous casting billet adopts hot delivery and hot charging process to save energy.

[0051] S3. Rolling: Steel rolling adopts a two-stage temperature-controlled rolling process. Roughing uses a high-temperature, high-reduction method, with an initial rolling temperature of 1125℃ and a cumulative reduction rate of 72.8%. The finishing rolling initial rolling temperature is 1012℃. During finishing rolling, the descaling water between the finishing stands, the roll gap cooling water, the inter-stand cooling water, and the cross-spray water are all shut off. The finishing rolling final temperature is 905℃; the final reduction rate of the finishing rolling pass is controlled at 10.5%, and the plate crown is controlled at 45±5μm.

[0052] S4, Laminar Flow Cooling: During the laminar flow cooling stage, no water is sprayed in actual production to obtain the required F+P microstructure, in which: ferrite accounts for 54% and pearlite accounts for 46%.

[0053] S5. Slow Cooling: After rolling, the steel coil is placed in a slow cooling pit for slow cooling for 50 hours to eliminate internal stress and improve the uniformity of microstructure and properties.

[0054] S6. Heat treatment: The process of normalizing + quenching + low-temperature tempering is adopted. The normalizing temperature is 875℃, the holding temperature is 31min, and the air cooling is applied. The quenching temperature is 920℃, the holding temperature is 31min, and the oil cooling is applied. After quenching, the low-temperature tempering is carried out in time. The tempering temperature is 280℃, the holding temperature is 26min, and the air cooling is applied to obtain the desired martensitic structure.

[0055] The test results of Example 1 show that the steel plate with dimensions of 16.0mm × 1850mm has a tensile strength R m 1825 MPa, yield strength Rp 0.2 1642 MPa, elongation after fracture A 50 Impact energy at -60℃: 14.5%, Kv2: 168 J, fracture toughness K1c: 152 MPa.m 1 / 2 With hardenability J51~55, the corrosion rate of low alloy steel Q355B is 34% under atmospheric corrosion environment.

[0056] Example 2:

[0057] A high-hardenability ultra-high-strength steel for aircraft landing gear has the following chemical composition by mass percentage: C: 0.35%, Si: 1.23%, Mn: 1.15%, P: 0.010%, S: 0.003%, Cr: 1.48%, Mo: 0.23%, V: 0.06%, Ti: 0.071%, B: 0.0054%, Alt: 0.024%, N: 0.0030%, O: 0.0010%. Further, B / N = 1.8, (Ce+Mg) / S = 2.4, with the balance being Fe and unavoidable impurities. In addition, the steel is required to have Pb+Sn+As+Sb+Bi ≤ 0.02%.

[0058] The method for preparing the high-hardenability ultra-high-strength steel for aircraft landing gear includes the following steps: The refining process uses an LF furnace ladle refining process, eliminating the RH stage and reducing costs. S1. Smelting: Top-and-bottom blown converter is used for smelting, with a scrap steel ratio of 42%. By limiting the scrap steel ratio, the carbon dioxide emissions during the preparation process are reduced.

[0059] Ladle furnace refining: Molten steel undergoes LF refining treatment, bottom blowing argon agitation, and the addition of submerged arc slag, refining slag, and lime. After heating for 16 minutes by energizing the three-phase electrodes, alloying elements are added for adjustment. Depending on the slag condition, aluminum granules and calcium carbide are added to create white slag. The energizing time is 21 minutes to adjust the alloy composition. Temperature is measured and samples are taken. If the composition and temperature meet the target requirements, soft blowing argon treatment is performed to ensure that the soft blowing + calming time reaches 24 minutes, so that inclusions can be fully floated and removed.

[0060] Continuous casting: A straight-arc continuous casting machine is used, with protective slag used throughout the process to prevent contact between the molten steel and air. The thickness of the continuously cast billet is 230mm. The feed rate of Ce-Fe cored wire is 17m / min, and the feed rate of Mg cored wire is 16m / min. The feed rate of Ce-Fe is 2.55kg / t steel, and the feed rate of Mg is 2.54kg / t steel. The casting speed is controlled at 1.26m / min. To reduce center segregation of the continuously cast billet, the superheat is controlled at 22℃, and electromagnetic stirring and dynamic light reduction technologies are used. The fixed length of the continuously cast billet is 11m.

[0061] S2. Heating: To ensure sufficient solid solution of BN, Ti(C,N), V(C,N), Cr3C2, Cr7C3, etc., the heating temperature is selected as 1260℃, the heating furnace is set to a weak oxidizing atmosphere, the air-fuel ratio is set at 1.14, and the heating time is controlled at 138min, of which the soaking time is 40min. The continuous casting billet adopts hot delivery and hot charging process to save energy.

[0062] S3. Rolling: Steel rolling adopts a two-stage temperature-controlled rolling process. Roughing uses a high-temperature, high-reduction method, with an initial rolling temperature of 1130℃ and a cumulative reduction rate of 73.2% during the roughing stage. The finishing rolling initial temperature is 1018℃. During finishing rolling, all descaling water between the finishing stands, roll gap cooling water, inter-stand cooling water, and cross-spray water must be shut off. The finishing rolling final temperature is 912℃. To ensure the flatness and precision of the finished steel plate, the reduction rate of the final finishing pass is controlled at 11%, and the plate crown is controlled within 45μm±5μm.

[0063] S4, Laminar Flow Cooling: During the laminar flow cooling stage, no water is sprayed in actual production to obtain the desired F+P microstructure. The microstructure consists of 55% ferrite and 45% pearlite.

[0064] S5. Slow Cooling: After rolling, the steel coil is placed in a slow cooling pit for slow cooling for 52 hours to eliminate internal stress and improve the uniformity of microstructure and properties.

[0065] S6. Heat Treatment: The process is as follows: normalizing temperature 882℃, holding for 26 min, air cooling; quenching temperature 914℃, holding for 38 min, oil cooling; after quenching, perform low-temperature tempering immediately at 286℃, holding for 21 min, air cooling. This yields the desired martensitic structure for the steel plate.

[0066] The test results of Example 2 show that the steel plate with dimensions of 12.0mm × 1900mm has a tensile strength Rm of 1850MPa and a yield strength Rp of 1850MPa. 0.2 1658 MPa, elongation after fracture A 50 Impact energy at -60℃: 15%, Kv2: 175 J, fracture toughness K1c: 160 MPa.m 1 / 2 Hardenability: J52~55, the corrosion rate of low alloy steel Q355B in atmospheric environment is 32%.

[0067] Example 3:

[0068] A high-hardenability ultra-high-strength steel for aircraft landing gear has the following chemical composition by mass percentage: C: 0.37%, Si: 1.25%, Mn: 1.25%, P: 0.012%, S: 0.002%, Cr: 1.53%, Mo: 0.26%, V: 0.06%, Ti: 0.063%, B: 0.0057%, Alt: 0.048%, N: 0.0038%, O: 0.0009%, B / N = 1.5, (Ce+Mg) / S = 2.0, with the balance being Fe and unavoidable impurities. Simultaneously, the steel must contain Pb+Sn+As+Sb+Bi ≤ 0.02%.

[0069] The method for preparing the high-hardenability ultra-high-strength steel for aircraft landing gear includes the following steps: The refining process uses an LF furnace ladle refining process, eliminating the RH stage and reducing costs. S1. Smelting: Top-and-bottom blown converter is used for smelting, with a scrap steel ratio of 47%. By limiting the scrap steel ratio, the carbon dioxide emissions during the preparation process are reduced.

[0070] Ladle furnace refining: Molten steel undergoes LF refining treatment, bottom blowing argon agitation, and the addition of submerged arc slag, refining slag, and lime. After heating for 16 minutes by energizing the three-phase electrodes, alloying elements are added for adjustment. Depending on the slag condition, aluminum granules and calcium carbide are added to create white slag. The energizing time is 24 minutes to adjust the alloy composition. Temperature is measured and samples are taken. If the composition and temperature meet the target requirements, soft blowing argon treatment is performed to ensure that the soft blowing + calming time reaches 22 minutes, so that inclusions can be fully floated and removed.

[0071] Continuous casting: A straight-arc continuous casting machine is used, with protective slag used throughout the process to prevent contact between the molten steel and air. The thickness of the continuously cast billet is 230mm. The feed rate of Ce-Fe cored wire is 17m / min, and the feed rate of Mg cored wire is 18m / min. The feed rate of Ce-Fe is 2.52kg / t steel, and the feed rate of Mg is 2.57kg / t steel. The casting speed is controlled at 1.30m / min. To reduce center segregation of the continuously cast billet, the superheat is controlled at 24℃, and electromagnetic stirring and dynamic light reduction techniques are used. The fixed length of the continuously cast billet is 11m.

[0072] S2. Heating: To ensure sufficient solid solution of BN, Ti(C,N), V(C,N), Cr3C2, Cr7C3, etc., the heating temperature is selected as 1267℃, the heating furnace is set to a weak oxidizing atmosphere, the air-fuel ratio is set at 1.16, and the heating time is controlled at 142min, of which the soaking time is 37min. The continuous casting billet adopts hot delivery and hot charging process to save energy.

[0073] S3. Rolling: Roughing adopts a high-temperature, high-reduction method, with an initial rolling temperature of 1128℃ and a cumulative reduction rate of 74.0% during the roughing stage; the finishing rolling initial rolling temperature is 1010℃; during finishing rolling, all descaling water between the finishing mill stands, roll gap cooling water, inter-stand cooling water, and cross-spray water must be shut off. The finishing rolling final temperature is 917℃; to ensure the flatness and precision of the finished steel plate, the reduction rate of the final finishing pass is controlled at 11.8%, and the plate crown target is controlled at 45μm±5μm.

[0074] S4, Laminar Flow Cooling: During the laminar flow cooling stage, no water is sprayed in actual production to obtain the desired F+P microstructure. The microstructure consists of 57% ferrite and 43% pearlite.

[0075] S5. Slow Cooling: After rolling, the steel coil is placed in a slow cooling pit for slow cooling for 53 hours to eliminate internal stress and improve the uniformity of microstructure and properties.

[0076] S6. Heat treatment: The process is as follows: normalizing temperature 880℃, holding temperature 34min, air cooling; quenching temperature 927℃, holding temperature 34min, oil cooling; after quenching, perform low-temperature tempering in time, tempering temperature 292℃, holding temperature 30min, air cooling, to obtain the required martensitic structure and properties.

[0077] The test results of Example 3 show that the steel plate with dimensions of 6.0mm × 1955mm has a tensile strength Rm of 1864MPa and a yield strength Rp of 1864MPa. 0.2 1662 MPa, elongation after fracture A 50 Impact energy at -60℃: 15.5%, Kv2: 182 J, fracture toughness K1c: 164 MPa.m 1 / 2Hardenability: J53~55, the corrosion rate of low alloy steel Q355B in atmospheric environment is 33%.

[0078] Example 4:

[0079] A high-hardenability, ultra-high-strength steel for aircraft landing gear has the following chemical composition by mass percentage: C: 0.37%, Si: 1.28%, Mn: 1.24%, P: 0.008%, S: 0.004%, Cr: 1.55%, Mo: 0.27%, V: 0.07%, Ti: 0.066%, B: 0.0052%, Alt: 0.052%, N: 0.0035%, O: 0.0008%, B / N = 1.49, (Ce+Mg) / S = 1.6, with the balance being Fe and unavoidable impurities. The steel is also required to have a Pb+Sn+As+Sb+Bi ≤ 0.02%.

[0080] The method for preparing the high-hardenability ultra-high-strength steel for aircraft landing gear includes the following steps: The refining process uses an LF furnace ladle refining process, eliminating the RH stage and reducing costs. S1. Smelting: Top-and-bottom blown converter is used for smelting, with a scrap steel ratio of 43%. By limiting the scrap steel ratio, the carbon dioxide emissions during the preparation process are reduced. Ladle furnace refining: Molten steel undergoes LF refining treatment, bottom blowing argon agitation, and the addition of submerged arc slag, refining slag, and lime. After heating for 16 minutes by energizing the three-phase electrodes, alloying elements are added for adjustment. Depending on the slag condition, aluminum granules and calcium carbide are added to create white slag. The energizing time is 23 minutes to adjust the alloy composition. Temperature is measured and samples are taken. If the composition and temperature meet the target requirements, soft blowing argon treatment is performed to ensure that the soft blowing + calming time reaches 23 minutes, so that inclusions can be fully floated and removed.

[0081] Continuous casting: A straight-arc continuous casting machine is used, with protective slag used throughout the process to prevent contact between the molten steel and air. The thickness of the continuously cast billet is 230mm. The feed rate of Ce-Fe cored wire is 18m / min, and the feed rate of Mg cored wire is 16m / min. The feed rate of Ce-Fe is 2.56kg / t steel, and the feed rate of Mg is 2.53kg / t steel. The casting speed is controlled at 1.28m / min. To reduce center segregation of the continuously cast billet, the superheat is controlled at 21℃, and electromagnetic stirring and dynamic light reduction technologies are used. The fixed length of the continuously cast billet is 11m.

[0082] S2. Heating: To ensure sufficient solid solution of BN, Ti(C,N), V(C,N), Cr3C2, Cr7C3, etc., the heating temperature is selected as 1272℃, the heating furnace is set to a weak oxidizing atmosphere, the air-fuel ratio is set at 1.18, and the heating time is controlled at 145min, of which the soaking time is 41min. The continuous casting billet adopts hot delivery and hot charging process to save energy.

[0083] S3. Rolling: Roughing employs high temperature and high reduction, with an initial rolling temperature of 1138℃ and a cumulative reduction rate of 74.5% during the roughing stage. The finishing rolling initial temperature is 1120℃. During finishing rolling, all descaling water between the finishing stands, roll gap cooling water, inter-stand cooling water, and cross-spray water must be shut off. The finishing rolling final temperature is 923℃. To ensure the flatness and precision of the finished steel plate, the reduction rate of the final finishing pass is controlled at 12.4%, and the plate crown target is controlled at 45μm±5μm.

[0084] S4, Laminar Flow Cooling: During the laminar flow cooling stage, no water is sprayed in actual production to obtain the desired F+P microstructure. The microstructure consists of 56% ferrite and 44% pearlite.

[0085] S5. Slow Cooling: After rolling, the steel coil is placed in a slow cooling pit for slow cooling for 52.5 hours to eliminate internal stress and improve the uniformity of microstructure and properties.

[0086] S6. Heat treatment: The process is as follows: normalizing temperature 887℃, holding temperature 31min, air cooling; quenching temperature 924℃, holding temperature 35min, oil cooling; after quenching, perform low-temperature tempering in time, tempering temperature 298℃, holding temperature 24min, air cooling, to obtain the desired martensitic structure.

[0087] The test results of Example 4 show that the steel plate with dimensions of 4.0mm × 2010mm has a tensile strength Rm of 1870MPa and a yield strength Rp of 1870MPa. 0.2 1665MPa, elongation after fracture A 50 Fracture toughness K1c: 16.5%, fracture toughness K1c: 165 MPa.m 1 / 2 Hardenability: J52~55, the corrosion rate of low alloy steel Q355B in atmospheric environment is 32%.

[0088] Obviously, the above embodiments are merely illustrative examples and not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A type of ultra-high strength steel for aircraft landing gear, characterized in that, The chemical composition of the steel, by weight percentage, is as follows: C: 0.35%–0.38%, Si: 1.22%–1.28%, Mn: 1.14%–1.29%, P≤0.012%, S≤0.004%, Cr: 1.44%–1.58%, Mo: 0.22%–0.28%, V: 0.05%–0.07%, Ti: 0.062%–0.074%, B: 0.0051%–0.0059%, Alt: 0.022%–0.054%, N: 0.0020%–0.0040%, O≤0.0010%, with B / N = 1.27–2.95, (Ce+Mg) / S = 1.5–3.0, and the balance being Fe and unavoidable impurities. The tensile strength R of steel m ≥1800MPa, yield strength R p0.2 ≥1600MPa, elongation after fracture A 50 ≥12%, impact energy Kv2≥160J at -60℃, fracture toughness K1c≥150MPa.m 1 / 2 Hardenability J51~55, corrosion rate ≤35% for low alloy steel Q355B in atmospheric environment; The preparation method of ultra-high strength steel for aircraft landing gear includes hot metal pre-desulfurization, top and bottom blowing converter smelting, LF ladle furnace refining, slab continuous casting, continuous casting billet heating, hot continuous rolling, laminar flow cooling, slow cooling and heat treatment. Specific methods include: The slab continuous casting includes: a Ce-Fe cored wire and a Mg cored wire feeding rate of 16-18 m / min, and a feeding amount of 2.52-2.58 kg / t steel; a casting speed of 1.22-1.32 m / min during casting; and a superheat of 22-26°C. The continuous casting billet heating includes: selecting a heating temperature of 1254-1274℃, setting the air-fuel ratio between 1.1 and 1.2, and controlling the heating time to 126 min-146 min, of which the soaking time is 32-42 min; The hot continuous rolling includes: an initial rolling temperature of 1122–1139℃ and a cumulative reduction rate of 72.4%–74.6% in roughing; an initial rolling temperature of 1010℃–1120℃ in finishing; and a final rolling temperature of 904–924℃ in finishing. The microstructure of the hot-rolled ultra-high strength steel for aircraft landing gear, by area percentage, is 53%–58% ferrite and 42%–47% pearlite. The ferrite matrix contains a large number of spherical Mn-O-Cr-Mo-BN composite inclusions, as well as composite inclusions of Ce, Mg and S, O. At the same time, there are also a large number of TiC, Ti(C,N) and BN precipitates with a size of less than 9.0 nm.

2. The ultra-high strength steel for aircraft landing gear according to claim 1, characterized in that, The residual elements in the steel are Pb+Sn+As+Sb+Bi≤0.02%.

3. The ultra-high strength steel for aircraft landing gear according to claim 1, characterized in that, The steel plate specifications are 3.0~16.0mm×1850~2150mm.

4. The method for preparing ultra-high strength steel for aircraft landing gear as described in any one of claims 1-3, characterized in that, This includes hot metal pre-desulfurization, top and bottom blowing converter smelting, LF ladle furnace refining, slab continuous casting, continuous casting billet heating, hot continuous rolling, laminar flow cooling, slow cooling, and heat treatment, without using RH refining; specific methods include: The slab continuous casting includes: a Ce-Fe cored wire and a Mg cored wire feeding rate of 16-18 m / min, and a feeding amount of 2.52-2.58 kg / t steel; a casting speed of 1.22-1.32 m / min during casting; and a superheat of 22-26°C. The continuous casting billet heating includes: selecting a heating temperature of 1254-1274℃, setting the air-fuel ratio between 1.1 and 1.2, and controlling the heating time to 126 min-146 min, of which the soaking time is 32-42 min; The hot continuous rolling includes: an initial rolling temperature of 1122–1139℃ and a cumulative reduction rate of 72.4%–74.6% in roughing; an initial rolling temperature of 1010℃–1120℃ in finishing; and a final rolling temperature of 904–924℃ in finishing.

5. The method for preparing ultra-high strength steel for aircraft landing gear according to claim 4, characterized in that: The top and bottom combined blowing converter smelting includes a scrap steel ratio of 41wt% to 48wt%.

6. The method for preparing ultra-high strength steel for aircraft landing gear according to claim 4, characterized in that: The LF ladle furnace refining process includes: soft blowing + quenching time of 21-26 minutes.

7. The method for preparing ultra-high strength steel for aircraft landing gear according to claim 4, characterized in that: The reduction rate of the final pass of finishing rolling is controlled at 10.2% to 12.4%, and the plate crown is controlled at 45±5μm. After rolling, the steel coil is placed in a slow cooling pit for slow cooling for no less than 48 hours.

8. The method for preparing ultra-high strength steel for aircraft landing gear according to claim 4, characterized in that: The heat treatment includes: normalizing at 874-889℃, holding for 25-35 minutes, and air cooling; quenching at 912-928℃, holding for 30-40 minutes, and oil cooling; and low-temperature tempering after quenching at 280-300℃, holding for 20-30 minutes, and air cooling.

Citation Information

Patent Citations

  • Round steel and preparation method and application thereof

    CN116926439A